2021
DOI: 10.1155/2021/1585692
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Analysis, In Vitro Evaluation of Alpha-Amylase, Alpha-Glucosidase, and Beta-Galactosidase Inhibition, and Antibacterial Activities of Juglans regia L. Bark Extracts

Abstract: In traditional medicine, various parts of the plant Juglans regia L. are used to treat several pathological conditions including diabetes and infectious and periodontal diseases. This includes the bark of Juglans regia. The present study is aimed at evaluating for the first time the mineral composition, investigating the antidiabetic and antibacterial properties of Moroccan J. regia bark, and finally determining the correlations between the chemical composition of the tested extracts and their biological activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…The nutraceutical properties of JKM, when used as food/feed supplements or ingredients, are revealed by the alpha-amylase inhibition (61.06%) and alpha-glucosidase inhibition (67.76%) capacities of JKM, as reported in this study (Figure 4). Previous research showed that phytogens had alpha-amylase and alpha-glucosidase inhibitory activities (Boulfia et al, 2021;Oloruntola & Ayodele, 2022). The phytochemical makeup of JKM may be responsible for its alpha-amylase and alpha-glucosidase inhibitory capabilities; for example, peptides derived from cereals, phenolic compounds, non-starch polysaccharides, and lipids were confirmed to inhibit alpha-glucosidase and alpha-amylase activities (Gong et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The nutraceutical properties of JKM, when used as food/feed supplements or ingredients, are revealed by the alpha-amylase inhibition (61.06%) and alpha-glucosidase inhibition (67.76%) capacities of JKM, as reported in this study (Figure 4). Previous research showed that phytogens had alpha-amylase and alpha-glucosidase inhibitory activities (Boulfia et al, 2021;Oloruntola & Ayodele, 2022). The phytochemical makeup of JKM may be responsible for its alpha-amylase and alpha-glucosidase inhibitory capabilities; for example, peptides derived from cereals, phenolic compounds, non-starch polysaccharides, and lipids were confirmed to inhibit alpha-glucosidase and alpha-amylase activities (Gong et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted on plants collected in the region of Taza, Morocco, have also revealed the richness of the said plants in mineral elements that are involved in their biological properties: Juglans regia has a high level of Fe (19849.8), K (3487.8), Mg (2631.03), and P (691.02 mg/kg), Leopoldia comosa is rich in Fe (33552), K (1843.14), P (756.36), Na (439.65), Cu (303.9), Mg (272.37), and Ca (20.55 mg/kg), and Ajuga iva has contents of 112.00 mg/l Fe, 44.071 mg/l K, and 16.572 mg/l Na [ 44 , 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, Singh and collaborators found that the highest antibacterial capacity was observed for sterols in E. hirta fruits (21 mm) [ 113 ]. In addition, studies conducted on plants from Taza region reported that Ajuga iva had the highest inhibition diameter for petroleum ether extract against Proteus mirabilis strain (14 mm) [ 91 ]; Juglans regia acetone macerate was found to be the most active with an inhibition diameter of 17 and 18 mm against Proteus mirabilis and Pseudomonas aeruginosa [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides J. regia septum, the effects on blood glucose of other matrices from this species were also evaluated. Boulfia et al showed that macerated acetone and ethanol extracts from walnut bark inhibited the activities of alpha-amylase and alpha-glucosidase [ 58 ]. These effects may be due to the various polyphenolics that were reported in walnut husk, buds, and bark [ 59 ].…”
Section: Biological Activitiesmentioning
confidence: 99%